Making the impossible, possible. Lessons learnt to ensure embodied physical education teacher education within COVID-19 times and beyond, regardless of the learning medium. Issue 2 (4th May 2022) - Howells, Kristy; Murray, Alison; Pearson, Julie; Whewell, Emma
ABSTRACT: This think piece discusses and examines how four teacher educators made what seemed like the impossible, possible. Through robust analysis of Newell's (1986) theoretical framework of constraints, we focused on developing innovative, creative, meaningful ideas to continue to effectively teach primary student teachers (students) how to teach physical education. This feat was attempted and attained in the absence of facilities, often without equipment and at times solely online. Physical education is understood through an embodied lived experience. Our findings share new ways of how to use constraints as a means to proactively attend to unforeseen subject enactment. We used the lens of the individual, environmental and task constraints to have positive lived embodied experiences of physical education. We found this was possible if the learning: was student centred; involved both student choice and voice; included sense making activities; involved team building collaborative activities and facilitated required digital fluency. We offer our thoughts as contextually framing guidance. We aspire to support and inspire the next generation of teachers in teaching physical education competently and confidently through all types of learning mediums that may be required in the future.